Nutritional Content of Catfish Nuggets from Aquaponic Cultivation - Pasaribu, Wesly; Pah, Theny Intan Berlian Kurniati; Fransira, Immaria; Djonu, Asriati; Boikh, Lebrina Ivantry (MultiTech Publisher, 2024)
Catfish (Clarias sp.) has high nutritional content. However, processed products such as nuggets from this fish are still limited in Kupang city. So, the nutritional content of the nuggets is less known. Therefore, this study aims to analyze the nutritional content of catfish nuggets derived from aquaponic cultivation, with proximate analysis. The stages of making catfish nuggets briefly begin with ground meat, then steamed, then coated with breadcrumbs and stored in the freezer. The proximate test obtained was the content of 11.67% protein, 30.139% carbohydrates, 7.82% fat, 48.137% water content, 2.22% ash and 0.014% crude fiber. So, with its nutritional content, catfish nuggets can be used as a substitute for chicken nuggets.